2016
DOI: 10.1007/s13311-016-0461-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined Metabolomics and Transcriptomics Approaches to Assess the IL-6 Blockade as a Therapeutic of ALS: Deleterious Alteration of Lipid Metabolism

Abstract: In amyotrophic lateral sclerosis (ALS), motor neuron degeneration occurs simultaneously with systemic metabolic impairment and neuroinflammation. Playing an important role in the regulation of both phenomena, interleukin (IL)-6, a major cytokine of the inflammatory response has been proposed as a target for management of ALS. Although a pilot clinical trial provided promising results in humans, another recent preclinical study showed that knocking out the IL-6 gene in mice carrying ALS did not improve clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…These observations are consistent with our findings, that is, identification of a perturbation of lactate metabolism from experiments obtained from spinal cord of SOD1 G93A mice. We previously observed no change in lactate level in the cortex of SOD1 G93A mice [results from previous study done by our team (Patin et al, )]. Importantly, as study design, disease evolution, brain regions and timing of sample collection were different, we consider that findings about the sense of metabolites levels changes are not comparable and cannot be interpreted.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…These observations are consistent with our findings, that is, identification of a perturbation of lactate metabolism from experiments obtained from spinal cord of SOD1 G93A mice. We previously observed no change in lactate level in the cortex of SOD1 G93A mice [results from previous study done by our team (Patin et al, )]. Importantly, as study design, disease evolution, brain regions and timing of sample collection were different, we consider that findings about the sense of metabolites levels changes are not comparable and cannot be interpreted.…”
Section: Discussionmentioning
confidence: 65%
“…We then aimed to compare these findings on astrocytes and extra‐cellular metabolic ALS signature with findings obtained from the cortex of mouse model of ALS [data not shown from a previous study done by our team (Patin et al, )]. An OPLS‐DA model and univariate analysis performed on cortex metabolites obtained from symptomatic transgenic SOD1 G93A mice revealed common discriminating metabolites between this in vivo model and our in vitro models (Table ).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Arginine/proline metabolism is an important metabolic pathway associated with neurodegenerative diseases (Patin et al, 2016b), and arginine and proline have been proposed as potential biomarkers of Alzheimer's disease recently (Ibanez et al, 2012). In present study, pathway analysis suggested that arginine/proline metabolism was the most important metabolic pathway in this process; in addition, arginine/proline metabolism was abnormal inflammation models (Drago et al, 2016; Patin et al, 2016a), which might suggest that sevoflurane induced neuroinflammation followed by altered arginine/proline metabolism and led to neurological damage ultimately.…”
Section: Introductionmentioning
confidence: 60%